Parameter Sifat Fisis dan Kuat Geser Tanah Lempung di Kawasan Tambak Desa Tambak Beras Kecamatan Cerme - satria (Jurnal Vokasi Teknik Sipil, 2025)
Tambak Beras Village, located in Cerme Subdistrict, Gresik Regency, is an area predominantly used for fish and shrimp farming, resulting in clay-dominated soil characteristics. This type of soil has low stability and is generally unsuitable for supporting construction activities. However, with the increasing development of warehouses and factories in the area, soil stabilization efforts are required to ensure the safety and sustainability of building structures. This study aims to identify the physical properties of clay soil in Tambak Beras Village through a series of laboratory tests. The method used is quantitative experimental research with sample testing based on the Indonesian National Standard (SNI). The tests conducted include water content, specific gravity, Atterberg limits, and soil shear strength. The results show that the soil has a water content of 98.32%, a specific gravity of 2.605 g/cc, and 97.80% passes through sieve No. 200. The liquid limit is 89.5%, plastic limit is 51.14%, and the plasticity index is 38.36%. The shear strength parameters indicate a cohesion (c) value of 7.366 kPa and an internal friction angle (φ) of 7.139°. Based on these findings, the clay soil in the study area has high plasticity and low bearing capacity, thus requiring further stabilization treatment to support safe and durable construction.